2022
DOI: 10.1088/1361-6633/ac42d9
|View full text |Cite
|
Sign up to set email alerts
|

The physics of empty liquids: from patchy particles to water

Abstract: Empty liquids represent a wide class of materials whose constituents arrange in a random network through reversible bonds. Many key insights on the physical properties of empty liquids have originated almost independently from the study of colloidal patchy particles on one side, and a large body of theoretical and experimental research on water on the other side. Patchy particles represent a family of coarse-grained potentials that allows for a precise control of both the geometric and the energetic aspects of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 222 publications
6
31
0
Order By: Relevance
“…
salient feature of liquid water is the anomalous behaviour of its thermodynamic response functions upon cooling, the most famous being the density maximum at ambient pressure [1][2][3][4][5][6] . In an effort to explain the origin of water's thermodynamic anomalies, enhanced in supercooled states, Poole et al suggested the presence of a first-order liquid-liquid phase transition (LLPT) line in the supercooled region of the pressure-temperature (P-T) phase diagram 7 .
…”
mentioning
confidence: 99%
“…
salient feature of liquid water is the anomalous behaviour of its thermodynamic response functions upon cooling, the most famous being the density maximum at ambient pressure [1][2][3][4][5][6] . In an effort to explain the origin of water's thermodynamic anomalies, enhanced in supercooled states, Poole et al suggested the presence of a first-order liquid-liquid phase transition (LLPT) line in the supercooled region of the pressure-temperature (P-T) phase diagram 7 .
…”
mentioning
confidence: 99%
“…Thus, at the triple point, the packing fraction ρv vdW with v vdW standing for the so-called van der Waals volumeis ∼38% for water and ∼60% for neon, argon, xenon, or krypton. The latter four are known to pertain to a broad class of liquids often referred to as “simple liquids.” Liquid water can be losely packed relative to simple liquids and, as such, is considered a representative member of the class of “empty liquids,” as patchy colloids are too …”
Section: Water As a One-component Fluidmentioning
confidence: 99%
“…Liquid water can be losely packed relative to simple liquids and, as such, is considered a representative member of the class of "empty liquids," as patchy colloids are too. 20 Simple liquids are understood from the classical interpretation of van der Waals theory due to H. C. Longhet-Higgins and B. Widom, which stresses that the packing effects inherent to the hard part of the pair potential largely determine the liquid's structure while attractive forces enter as a perturbation. This picture is, however, incapable to sustain a ρv vdW value as low as the one of liquid water.…”
Section: Water As a One-component Fluidmentioning
confidence: 99%
See 1 more Smart Citation
“…This makes the assembly particularly difficult for the isotropic and short-range potentials that typically govern colloidal particles, and which tend to favour close-packed structures. To overcome this problem, one of the most promising approaches has been to use anisotropic interactions, 9 and in particular colloidal particles with tetrahedrally arranged bonding sites. These particles are termed Patchy Particles (Fig.…”
mentioning
confidence: 99%